2014
DOI: 10.1002/jrsm.1111
|View full text |Cite
|
Sign up to set email alerts
|

Learning by doing—teaching systematic review methods in 8 weeks

Abstract: Our experiences have led us to remain committed to a hands-on approach. Our course serves as a bridge between classroom learning and real-world practice, and provides an example of teaching systematic review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…Our workshop participants expressed similar attitudes in Survey I, in which both the lectures and the hands‐on exercises were found to be useful. However, other studies have found overall preference for practical activities 33 , 35 . The participative and interactive format used in our workshops was perceived as beneficial for attendees to learn the EBD concepts.…”
Section: Discussionmentioning
confidence: 70%
“…Our workshop participants expressed similar attitudes in Survey I, in which both the lectures and the hands‐on exercises were found to be useful. However, other studies have found overall preference for practical activities 33 , 35 . The participative and interactive format used in our workshops was perceived as beneficial for attendees to learn the EBD concepts.…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, the model allows participants easy access to peer reviewers through a peer discussion of their protocols. The participants may have played a role similar to that of teaching assistants in the previously reported university course, leading to the success of this workshop [26]. A notable success story is when one of the participants (MB), who was new to SR during the third WS, became a competent tutor in the eighth and ninth WSs, contributing greatly to the WS's sustainability.…”
Section: Discussionmentioning
confidence: 90%
“…Faculty members were the primary instructors for all the courses, and the sole instructors for seven. Five articles (Briner & Walshe, 2014;Gorczynski et al, 2017;Groller et al, 2020;Li et al, 2014;Proly & Murza, 2009) explicitly mention librarian involvement either within the original course or as a modification for later offerings based on feedback. The course objectives generally focus on students developing an understanding of reviews and the skills to conduct one.…”
Section: Stand Alone Workhopsmentioning
confidence: 99%
“…The course objectives generally focus on students developing an understanding of reviews and the skills to conduct one. Some unique objectives include learning to teach others about systematic reviews (Li et al, 2014) and gaining project management skills and leadership experience (Proly & Murza, 2009). The articles present a variety of graded assignments designed to assess student learning, many of them tied to specific steps of the review process.…”
Section: Stand Alone Workhopsmentioning
confidence: 99%
See 1 more Smart Citation